Penguatan Literasi Digital dalam Meningkatkan Kesadaran Politik Warga di Desa Kuripan Ciseeng Bogor - Rosit, Muhamad; Al Katiri, Jufri; Rifansya, Firly Putri (Penerbit Widina, Widina Media Utama, 2024)
This Community Service (PKM)program aims to enhance political literacy of the residents of Kuripan, Ciseeng, Bogor, trough strengthening digital literacy. Digital literacy serves as a key enabler in facilitating the community’s access to credible and high-quality political information on social media. The program focuses on empowering residents to use digital technology and media to access, comprehend, and analyse a variety of political information. Trough a series of training sessions and mentoring, the program aspires to raise political awareness among villages and foster their active participation in democratic political processes. The digital literacy training has improved participants’ ability to access political information on the internet, verify the authority of news source, share political information on social media, an utilize sources to seek political information. However, participants’ involvement in political discussion on social media shown only a slight increase, from 10% to 30%. This serves as a benchmark indicating the need for greater and further efforts to significanly enhance this aspect.ABSTRAKPengabdian kepada Masyarakat (PKM) ini bertujuan untuk meningkatkan kesadaran literasi politik warga Kuripan Ciseeng Bogor melalui penguatan literasi digital. Literasi digital menjadi kunci utama dalam memfasilitasi akses warga desa terhadap berbagai informasi politik yang kredibel di media sosial. Fokus program ini pada pemberdayaan warga dalam menggunakan media digital untuk mengakses, memahami, dan menganalisis ragam informasi politik. Melalui serangkaian pelatihan dan pendampingan, diharapkan warga desa memiliki peningkatan kesadaran politik dan lebih partisipatif dalam proses politik demokratis. Hasil pelatihan literasi digital ini meningkatkan warga dalam mengakses informasi politik di internet, mampu memverifikasi keaslian sumber berita, berbagi informasi politik di media sosial dan menggunakan berbagai sumber dalam mencari informasi politik, namun keterlibatan peserta dalam diskusi politik di media sosial masih menunjukkan peningkatan rendah dari 10% menjadi 30%. Hal ini menjadi alat ukur bahwa memerlukan perhatian dan upaya lebih lanjut untuk ditingkatkan secara signifikan.